Perioperative changes in prouroguanylin hormone response in severely obese subjects after bariatric surgery - Alfonso Torquati (2020)
© 2019 Elsevier Inc. Background: Prouroguanylin is a gut hormone converted into uroguanylin in the hypothalamus. Uroguanylin induces satiety through guanylyl-cyclase-2C receptor signaling. However, little is known about the role of this hormone in regulating human food intake. Methods: In prospective-cohort study, prouroguanylin profile changes were determined during meal stimulation in obese patients 2 weeks before and 2 weeks after Roux-en-Y gastric bypass surgery. We also investigated whether these changes play a role in the anorexigenic effect of Roux-en-Y gastric bypass. Results: The study enrolled 8 healthy lean volunteers and 10 obese patients with type 2 diabetes. Prouroguanylin levels were postprandially decreased at 30 minutes (P =.04) and 60 minutes (P =.008) in obese patients before surgery, and they were increased at 60 minutes (P =.003), 90 minutes (P =.008), and 120 minutes (P =.009) after surgery. We observed a significant difference (P =.001) in fasting prouroguanylin levels before (8.82 ± 1.2 ng/mL) and after (6.05 ± 1.2 ng/mL) Roux-en-Y gastric bypass. Hunger ratings in the fasted state did not change after Roux-en-Y gastric bypass. Instead, subjects demonstrated significantly (P =.01) lower hunger visual analog scale scores than before Roux-en-Y gastric bypass. No correlations between circulating prouroguanylin levels and hunger perception were found before or after Roux-en-Y gastric bypass. Conclusion: Prouroguanylin levels decrease after meal stimulation in obese patients, and they increase after Roux-en-Y gastric bypass, but no correlations exist with hunger visual analog scale scores.